Gambaran Tingkat Stress pada Lansia di Era New Normal: Overview of Stress Levels in the Elderly in the New Normal Era - saelan; Aliffia Esprensa; Martina Ekacahyaningtyas (LPPM STIKES NOTOKUSUMO YOGYAKARTA, 2022)
Stress is the body's response to psychosocial stressors. Changes that occur in the elderly such as deterioration in physical condition, chronic illness, weakness or fragility, and loss of ability to carry out daily activities can cause changes in the psychological state. It can also be a stressor that is often felt by the elderly. During the COVID-19 pandemic, the elderly has a high risk of transmitting the virus. The implementation of the New Normal concept is a trigger for stress in the elderly. The purpose of this study was to analyze the description of stress levels in the elderly in the New Normal era at the Aisyiyah Nursing Home, Surakarta. This research is a qualitative research with a descriptive approach. This study uses a survey research method (research method) as a research design. The sampling technique was carried out by total sampling technique with the number of research respondents as many as 30 people. The measuring tool for the success of describing stress levels in the elderly in the New Normal Era in this study used the DASS (Depression Anxiety Stress Scale) questionnaire. Data analysis in this study used univariate analysis to describe each variable. The results of this study indicate that most of the stress in the elderly is in normal conditions (56.7%) with an average age of 60-74 (50.0%). Meanwhile, in terms of gender, women were (100%). Keywords: Stress, Elderly, New Normal